Sensación térmica en aulas del pabellón A10 de la Facultad de Agronomía. Loreto, 2024 - Apagueño Sajami, Maryori (2024)
This research examines how variations in temperature and humidity affect thermal comfort in Hall A10 throughout the day and between different floors of the building. The results indicate that thermal sensation varies significantly depending on the time of day and external conditions, such as solar radiation. On warm days, internal temperatures can exceed 29°C on the first floor and 32°C on the third floor, where conditions are especially uncomfortable due to heat buildup and low relative humidity. On the other hand, on cool days, the temperature remains more stable and comfortable. Furthermore, the increase in temperature in the classroom during the hours of greatest solar radiation and the concentration of students in small areas contribute to a more intense thermal sensation. These findings suggest that both external conditions and the distribution of people in the classroom have an important impact on thermal comfort, highlighting the need to improve ventilation and consider design.